Korelasi Konsentrasi Black Tea Powder (Camelia sinensis) terhadap Muiu Sensori Produk Dark Chocolate - Yusep Ikrawan; Hervelly Hervelly; Wandy Pirmansyah (Pasundan Food Technology Journal (PFTJ), 2019)
The purpose of this research is to learn the correlation of black tea powder against sensory level alteration of dark chocolate. The benefits of this research are to learn and give the information about the application of black tea powder as one of diversified products of dark chocolate process and provide information on the appropriate quality of dark chocolate products with the addition of black tea powder. The research method used is simple linear regression. The used factor is the variance of black tea powder concentration 0%, 2%, 3% and 4%. Physical response of dark chocolate product with the addition of black tea powder which is color and texture (hardness and stickiness) and organoleptic test which is consumen acceptance test based on scoring test on the attribute of sweet taste, bitter taste, specific aroma of black tea and texture. The result showed thet the code sampel A1( black tea powder 2%) is a dark chocolate product with the addition of selected black tea powder based on consumen acceptance test which is scoring test.